Von Wasserwerfern und Mikrowellen: Überlegungen zu einer Typologie innovatorischen Scheiterns - Bauer, Reinhold (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2006)
Innovation failure, not success, is the norm. As such, it is of major importance for the understanding of technological change. In this paper four examples for failure will be presented. By snatching these “blots” from oblivion some typical reasons for failure shall be elucidated.